Canada's labour market training system - Barnetson, Bob, 1970- (Open paths to enriched learning., 2018)
How does the current labour market training system function and whose interests does it serve? In this introductory textbook, Bob Barnetson wades into the debate between workers and employers, and governments and economists to investigate the ways in which labour power is produced and reproduced in Canadian society. After sifting through the facts and interpretations of social scientists and government policymakers, Barnetson interrogates the training system through analysis of the political and economic forces that constitute modern Canada. This book not only provides students of Canada's div.